2017
DOI: 10.20885/jsb.vol21.iss1.art2
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh integrasi, berbagi informasi, dan penundaan pada kinerja rantai pasokan: Studi pada usaha kecil menengah batik di Indonesia

Abstract: This study focuses on the effect of five supply chain practices: supplier integration, internal integration, customer integration, information sharing, and postponement on supply chain performance. We conducted a survey by distributing questionnaires to 102 companies in the sector of batik in Surakarta, using purposive sampling. The findings show that in general, supply chain practices have impact on supply chain performance. More specifically, the internal integration and information sharing have significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(44 reference statements)
0
8
0
2
Order By: Relevance
“…The impact of information sharing on business performance has been widely studied, with the results indicating a positive correlation between the two. Mufaqih et al (2017) found that companies that practice effective information sharing can improve their performance, while Hardiana and Setiawan (2021) stated that companies with better supply chain management (SCM) tend to have improved operational performance. Huda et al (2018) conducted research and they found that information sharing has a significant positive effect on company performance, suggesting that the better the information sharing, the higher the impact on company performance.…”
Section: Relationship Of Information Sharing With Business Performancementioning
confidence: 99%
“…The impact of information sharing on business performance has been widely studied, with the results indicating a positive correlation between the two. Mufaqih et al (2017) found that companies that practice effective information sharing can improve their performance, while Hardiana and Setiawan (2021) stated that companies with better supply chain management (SCM) tend to have improved operational performance. Huda et al (2018) conducted research and they found that information sharing has a significant positive effect on company performance, suggesting that the better the information sharing, the higher the impact on company performance.…”
Section: Relationship Of Information Sharing With Business Performancementioning
confidence: 99%
“…Google menjadi salah satu mesin pencari yang populer yang digunakan untuk mencari berbagai macam informasi termasuk informasi tentang pemasaran. Informasi pemasaran menjadi sangat penting dalam menunjang hubungan antara produsen dan konsumen [1]. Pencarian kata kunci pemasaran pada mesin pencari dapat menjadi informasi yang dapat dimanfaatkan dalam pemasaran online.…”
Section: Abstract-marketing Content; Online Platforms; Search Engine ...unclassified
“…So the performance of this sector must be supported by good management. Empirical research has found that internal integration and information sharing have a significant positive effect on supply chain performance (Mufaqih, Indarti, Ciptono, & Kartikasari, 2017). Uniquely, the postponement has a negative impact on supply chain performance.…”
Section: Empiricalmentioning
confidence: 99%